QUALITATIVE COMPARATIVE ANALYSIS (QCA) IN EDUCATION MANAGEMENT RESEARCH - Tubagus Syihabudin; M. Luthfi; Siti Ngaisah; Eneng Muslihah (EZRA SCIENCE BULLETIN, 2025)
The research aims to analyse the potential application of the Qualitative Comparative Analysis (QCA) method in uncovering the configuration of managerial factors that contribute to the effectiveness of education management, and to evaluate the relevance of QCA as a set-theoretical approach in strategic decision-making of the Internal Quality Assurance System (SPMI) in higher education. This research employs a qualitative approach, drawing on systematic literature reviews and case studies from educational management, particularly those examining university governance and institutional performance. The results show that (QCA) has a strong potential to uncover the configuration of managerial factors that contribute to the effectiveness of education management and the (SPMI) in higher education, not through a single variable but through a combination of conditions such as the strength of SPMI implementation, the application of Good University Governance (GUG) principles, Leadership support, and a consistent quality evaluation system. This research contributes by offering a conceptual framework for applying QCA in educational management and by providing research recommendations.